Exploring the contributions of non-farm income diversification for improving soil and water conservation practices and reducing rural poverty in rain-fed areas of Punjab, Pakistan - Jabbar, Awais; Wei, Liu; Zhang, Jian; Liu, Jiyun; Wang, Ye; Wu, Qun; Peng, Jianchao (Frontiers in Sustainable Food Systems, 2023)
Attaining agricultural sustainability and eliminating poverty are the key challenges of rural areas. Non-farm income diversification is a vital livelihood strategy that endorses sustainable agriculture and alleviates poverty. Considering the land degradation and poor economic situation of Pakistan's rain-fed areas, the current research examined the potential effects of non-farm income diversification on household poverty and adopting soil and water conservation (SWC) technologies. A survey of 441 farmers was conducted in rain-fed areas of Punjab, Pakistan, and for econometric analysis, the propensity score matching (PSM) technique was employed to explore the objectives. The results signified that diversified farmers were more likely to adopt SWC practices and were less vulnerable to poverty. The findings suggest that farmer-based organizations and agricultural extension activities must be strengthened as they support non-farm income diversification, thus facilitating investment in soil and water conservation technologies and reducing poverty.